Telemetry Temperature Measurement Based on FM Radio Frequency - Sutarta Tarta; Arief Marwanto; Suryani Alifah (Universitas Islam Sultan Agung, 2020)
Telemetry systems have been widely used in industrial machines to continuously monitor movement and data from industrial machinery. However, obstacles occured in areas that have not been reached by cellular or internet signals such as mining areas and oil palm plantations. One machine that requires continuous attention is the Genset engine or power plant. Howevwr, the officers had to be placedon that site or are not effectively. Therefore it is necessary to make remote monitoring and control to determine the condition of the generator, especially the generator temperature, because of the temperature indicator can be known the performance and efficiency of the generator. The information of generator indicates the performance of generator, such as temperature and fuel comsumtion. A monotoring should done remotaly wheneverrural areas are further away from the head master offices. Real time monitoring proposed where able to change and control generator. FM transceiver used to addressing the limitation of protocil communication or rural areas since the GSM signals and internet are not coveraged that areas. Half duplex protocol communication is proposed to manage data exchange between Tx and Rx. The result show that protocol work performing during data transmision in simulation mode, however data lossed at 515 meters due to small power trancmitter is used.